STUDY OF THE ETHNIC COMPOSITION OF THE POPULATION OF THE ZARAFSHAN OASIS IN THE 19TH AND FIRST QUARTER OF THE 20TH CENTURIES - Kulmatov Dilmurod Khidirovich (Bright Mind Publishing, 2025)
This article examines the beginning of a new phase of ethnographic research on the population of Central Asia in the 1920s. The nature and significance of ethnographic research during this period are analyzed in historical studies.
Keywords: World civilizations, Turkic ethnic groups, Muslims, migration processes